Analytical and Experimental Analysis on Kinetics of a Laparoscopic Surgery Tool - Özin, Mithat Can; Vatansever, Emre; Eray, Turgay; Koç, İlker Murat; Sümer, Bilsay (ACM, 2017)
Each laparoscopic surgery tool has specific design and task, which includes grasping, cutting, clamping, retraction etc. for surgery. This study deals with kinetic analysis of a conventional laparoscopic grasper in order to obtain a simple and valid analytical model that allows optimization of tool dimension, and verification of the model with experimental results. Additionally, simplified analytical model is compared with previously developed analytical model. The simplified model has the same results in calculation of actuator and grasper force compared to its predecessor. With the simplified analytical model, maximum error between the analytical and the experimental results is up to 2.8% in specific parameters.